1992
DOI: 10.1080/13854049208401850
|View full text |Cite
|
Sign up to set email alerts
|

The MMPI and closed-head injury

Abstract: This study examined Minnesota Multiphasic Personality Inventory profile configuration in matched samples of males (n = 77) and females (n = 25) suffering from closed-head injury. For the males, the mean group high-point was the 5c scale; the mean group high-point for the females was the D scale. For the males, the mean group two-point code was the 8-2 configuration; the mean group two-point code for the females was the 2-3 configuration. The males as a group also scored significantly higher than the females on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The group with MTBI also differed significantly from the WAD and control groups with respect to the representation of males and females. Given the possibility of sexrelated differences in emotional functioning following TBI [38], this difference between the groups represents a potential limitation to the generalizabilty of the results of this study. Examination of sexrelated differences in emotional functioning following MTBI represents a direction for future research that would have both theoretical and practical importance.…”
Section: Discussionmentioning
confidence: 88%
“…The group with MTBI also differed significantly from the WAD and control groups with respect to the representation of males and females. Given the possibility of sexrelated differences in emotional functioning following TBI [38], this difference between the groups represents a potential limitation to the generalizabilty of the results of this study. Examination of sexrelated differences in emotional functioning following MTBI represents a direction for future research that would have both theoretical and practical importance.…”
Section: Discussionmentioning
confidence: 88%
“…It is a paper and pencil test consisting of 567 true-false questions that can be answered by any adult who has a sixth-grade education. It is simple to administer and take and is the most widely used instrument in forensic evaluation (Borum & Grisso, 1995;Keilen & Bloom, 1986;Lees-Haley, Smith, Williams, & Dunn, 1996), including those involving personal injury, emotional harm, workers compensation, pain, and disability (Boccaccini & Brodsky, 1999;Butcher, 1985;Bradley, Prokop, Margolis, & Gentry, 1978;Fordyce, 1979;Keller & Butcher, 1991;Shaffer, 1981;Shaffer, Nussbaum, & Little, 1972;Alfano, Neilson, Paniak, & Finlayson, 1992). One survey of 100 examiners conducting personal injury examinations on adults found that the MMPI was the second most frequently used psychological test, ranking behind the Wechsler Adult Intelligence Scale (Lees-Haley et al, 1996).…”
Section: The Use Of the Mmpi-2 In Courtmentioning
confidence: 98%
“…For example, several studies have shown that the incidence of emotional problems following acquired brain injuries can be as high as 6O%, particularly in relation to depression and anger (Alfano, Neilson, Paniak, & Finlayson, 1992 ;Brooks, Campsie, Symington, Beattie, & McKinlay, 1986). The incidence of emotional disorders has been found to be slightly lower among those with spinal injuries than among those with brain injuries (Stambrook et al, 1991).…”
Section: Psycho Log Ica 1 Impactmentioning
confidence: 98%